Anticancer agents interacting with membrane glucose transporters. Issue 9 (21st July 2016) - Granchi, C.; Fortunato, S.; Minutolo, F.
Abstract : The altered metabolism observed in cancer cells generally consists of increased glucose uptake and glycolytic activity. Abstract : The altered metabolism observed in cancer cells generally consists of increased glucose uptake and glycolytic activity. This is associated with an overexpression of glucose transporter proteins (GLUTs), which facilitate glucose uptake across the plasma membrane and play a crucial role in the survival of cancer cells. Therefore, GLUTs are considered as suitable targets for treatment of cancer. Herein we review some of the most relevant GLUT inhibitors that have been recently developed as prospective anticancer agents.